#CoronavirusCruise: Impact and implications of the COVID-19 outbreaks on the perception of cruise tourism. (January 2022) - Muritala, Babajide Abubakr; Hernández-Lara, Ana-Beatriz; Sánchez-Rebull, Maria-Victoria; Perera-Lluna, Alexandre
Abstract: Early in the COVID-19 pandemic, the Diamond Princess became the center of the largest outbreak outside the original epicenter in China. This outbreak which left 712 passengers infected and 14 dead, followed by subsequent outbreaks affecting over one-third of the active ships in the cruise industry's global fleet, quickly became a crisis that captured public attention and dominated mainstream news and social media. This study investigates the perception of cruising during these outbreaks by analyzing the tweets on cruising using Natural Language Processing (NLP). The findings show a prevalent negative sentiment in most of the analyzed tweets, while the criticisms directed at the cruise industry were based on perceptions and stereotypes of the industry before the pandemic. The study provides insight into the concerns raised in these conversations and highlights the need for new business models outside the pre-pandemic mass-market model and to genuinely make cruising more environmentally friendly. Highlights: We evaluate the perception of cruising from conversations on Twitter around the COVID-19 outbreaks. About half of the analyzed tweets carried a negative sentiment, an expected but important result. Criticisms were mostly based on stereotypes and perceptions of cruising before the pandemic. Many of the criticized aspects of cruising are associated with the pre-pandemic mass-market cruise model. The cruise industry needs new sustainable business models post-COVID-19.